PERBEDAAN JUMLAH BAKTERIURI PADA WANITA LANJUT USIA BERDASARKAN KULTUR MIKROBIOLOGI MENGGUNAKAN TEKNIK CAWAN TUANG DAN CAWAN SEBAR - Ni Wayan Evi Damayanti; Moh Fairuz Abadi; Ni Wayan Desi Bintari (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2020)
Introduction: Bacteriuri are the presence of bacteria present in the urine that can cause urinary tract infections. Bacterial examination can be carried out by microbiological culture methods using pour plate and spread plate techniques Objective: This study aims to determine the differences in the results of the application of pour plate and spread plate techniques to the number of bacteriuri found in elderly women. Method: The type of research used is experiment. This research was conducted in April 2019. The examination site was conducted at the Bacteriology Laboratory, Study Program of Medical Laboratory Technology, STIKes Wira Medika Bali. The sample of this study was 14 respondents. The sampling technique was purposive sampling with inclusion and exclusion criteria. Data were analyzed using the T test. Results: The results of statistical analysis showed a value of p 0.05, which means that H0 was accepted, so there was no difference in the number of bacteriuri examined by microbiological culture using pour plate and spread plate techniques